PENGARUH KEMAMPUAN MANAJERIAL PIMPINAN TERHADAP KEBERHASILAN PROGRAM KURIKULUM BERBASIS KOMPETENSI - -, Sumaryanto - (JURNAL MANAJEMEN SUMBER DAYA MANUSIA, 2007)
ABSTRAK Target in this research is to know influence significance ability of dean managerialÂ  covering ability of planning, organizing, directing, and controlling to efficacy of curriculum program base on competition in Economic Faculty of Unisri, either through partial and by together. To be can finish head duty better as according to owned profession, dean require to have and master ability of managerial, so that can run duty lead and can improve performance all led lecturer. Concluded by planning, organizing, directing, and controlling by partial and also together have an effect on significant to curriculum program variable base on competition . Result of determination coefficient obtained by R2 value = 0,792, meaning independent variable contribution to dependent variable equal to 79,2 percent, while the rest 20,8 percent influenced by other variable which is not checked Keywords: planning, organizing, directing, controlling, curriculum program base on competition